Interrogaring Caste/ Understanding Hierarchy & Difference in Indian Society - Gupta,Dipankar
The caste system has conventionally been perceived by scholars as a hierarchy based on the binary opposition of purity and pollution. Challenging this position, leading sociologist Dipankar Gupta argues that any notion of a fixed hierarchy is arbitrary and valid only from the perspective of the individual castes. The idea of difference, and not hierarchy, determines the tendency of each caste to keep alive its discrete nature and this is also seen to be true of the various castes which occupy the same rank in the hierarchy. It is, in fact, the mechanics of power, both economic and political, that set the ground rules for caste behaviour, which also explains how traditionally opposed caste groups find it possible to align in the contemporary political scenario. With the help of empirical evidence from states like Bihar, Maharashtra and Uttar Pradesh, the author illustrates how any presumed correlations between caste loyalties and voting patterns are in reality quite invalid. Provocative and finely argued, Interrogating Caste is a remarkable work that provides fresh insight into caste as a social, political and economic reality.